Economic impacts of electricity supply shortages in South Africa - Hiroaki Suenaga (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
This study examines the sectoral impacts of electricity supply shortages in South Africa, using the cost share information available from the 2015 social accounting matrix. A simulation conducted under each of two technological assumptions, Cobb-Douglas and Leontief, reveals that a productivity decline in the electricity, gas, steam, and hot water supply (EGSH) sector increases the price of the EGSH sector substantially, while it affects the other sectors marginally due to the small cost shares of the EGSH factor in these sectors. The total cost of supplying the baseline final demand increases by ZAR19 billion or 0.46% of the baseline gross value added (GVA) when EGSH productivity declines by 10%. This cost impact expands to ZAR150 billion or 3.57% of GVA when EGSH productivity is halved. Large shares of these cost increments are incurred by the EGSH and manufacturing sectors, owning to the direct physical impact of productivity decline for the former and a large share of its sectoral GVA in the aggregate economy for the latter. The simulation also indicates that the equilibrium wage should increase by a greater extent for workers with a lower education than for those with a higher education if the baseline final demands are to be met at the higher EGSH output price after the sector's productivity decline.
Keywords: D57; D58; Q43; 330; electricity supply shortage; equilibrium price model; South Africa